2017
DOI: 10.3233/bir-16107
|View full text |Cite
|
Sign up to set email alerts
|

Effect of circulating tissue factor on hypercoagulability in type 2 diabetes mellitus studied by rheometry and dielectric blood coagulometry

Abstract: Background:Hypercoagulability in type 2 diabetes mellitus (T2DM) patients increases their risk of cardiovascular diseases.Objective:The aim of this work was to investigate the hypercoagulation mechanism in T2DM patients in terms of circulating tissue factor (TF).Methods:Whole blood coagulation tests by damped oscillation rheometry and dielectric blood coagulometry (DBCM) were performed.Results:The average coagulation time was significantly shorter for T2DM patients than for healthy controls. In vitro addition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Whole blood coagulation tests such as thromboelastography [ 1 ], rotational thromboelastometry [ 2 ] and recently developed dielectric blood coagulometry (DBCM) [ 3 ] are intended for the evaluation of comprehensive blood coagulability. It has also been reported that DBCM is highly sensitive to hypercoagulability in patients with diabetes [ 4 ] or respiratory diseases [ 5 ], and it is also promising for risk assessment of stroke [ 6 ] and prediction of venous thromboembolism after total knee arthroplasty [ 7 ]. In DBCM, as well as thromboelastometry, Ca 2+ is commonly used to restart the blood coagulation process on citrated blood.…”
Section: Introductionmentioning
confidence: 99%
“…Whole blood coagulation tests such as thromboelastography [ 1 ], rotational thromboelastometry [ 2 ] and recently developed dielectric blood coagulometry (DBCM) [ 3 ] are intended for the evaluation of comprehensive blood coagulability. It has also been reported that DBCM is highly sensitive to hypercoagulability in patients with diabetes [ 4 ] or respiratory diseases [ 5 ], and it is also promising for risk assessment of stroke [ 6 ] and prediction of venous thromboembolism after total knee arthroplasty [ 7 ]. In DBCM, as well as thromboelastometry, Ca 2+ is commonly used to restart the blood coagulation process on citrated blood.…”
Section: Introductionmentioning
confidence: 99%